Friday

November 28, 2014

November 28, 2014

Posted by **laci** on Monday, October 12, 2009 at 9:43pm.

- algebra -
**PsyDAG**, Tuesday, October 13, 2009 at 10:50amI assume that you mean:

(3x^2 - 10x)/(x-6) = (3x + 8 + 48)/(x-6)

If so, multiply both sides by x - 6.

3x^2 - 10x = 3x + 56

Subtract 3x from both sides.

3x^2 - 13x = 56

Factor out x to give you:

x(3x -13) = 56

x = 56 or

3x - 13 = 56

3x = 69

x = 23

I hope this helps. Thanks for asking.

**Answer this Question**

**Related Questions**

Algebra - please show steps solve 9 - (9)squared > 10x - x

Algebra - This question never got answered and I would appreciate it if someone ...

Algebra I - Thanks Reiny, but I'm still lost. I understand how you multipled by ...

(pls help) algebra - 4x+y-32=1, 6x-y-4z=7, 10x+2y-6z=5 pls show me how to solve ...

Math - Determine the zeros of the function 3x^2 -8=10x. I know I rewrite it as ...

Algebra - i need to use the quadratic formula 2 solve these 4 questions: 1. x(...

algebra - Gina wrote this system of linear equations: 2x + y = 7 4x + 5y = 11 ...

Algebra - Determine the zeros of the function 3x^2 -8=10x. I know I rewrite it ...

Algebra - 17-Identify the vertex, axis of symmetry and x-intercept(s) of F(x)=(x...

math - How do i find the area of a triangle? For example: A squared + b squared...